2017
DOI: 10.1007/s00464-017-5741-4
|View full text |Cite
|
Sign up to set email alerts
|

Pure laparoscopic radical resection for type IIIa hilar cholangiocarcinoma

Abstract: Background Pure laparoscopic radical resection of hilar cholangiocarcinoma is still a challenging procedure, in which laparoscopic lymphadenectomy, hemihepatectomy with caudate lobectomy, and hepaticojejunostomy were included [1][2][3][4]. Relative report is rare in the world up to now. Hilar cholangiocarcinoma has a poor prognosis, especially when it occurs with lymph node metastasis or vessel invasion [5,6]. We recently had a patient who underwent a pure laparoscopic extended right hepatectomy and lymph node… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 6 publications
1
19
0
Order By: Relevance
“…Indications for minimally invasive liver surgery has historically changed, starting with minor, regulated resections expanding to embrace major and extended hepatic surgery, including ALPPS, posterior segments, hilar tumors, and living‐donor hepatectomy . We can speculate that indications to convert changed as well.…”
Section: Discussionmentioning
confidence: 99%
“…Indications for minimally invasive liver surgery has historically changed, starting with minor, regulated resections expanding to embrace major and extended hepatic surgery, including ALPPS, posterior segments, hilar tumors, and living‐donor hepatectomy . We can speculate that indications to convert changed as well.…”
Section: Discussionmentioning
confidence: 99%
“…Noncomparative studies are demonstrated in Table , and their pooled analysis has shown that 90% of the patients were submitted to major liver resections (ES, 0.9; 95% CI, 0.68‐1.00/heterogeneity I 2 = 0%; Figure E) . Also, it was obtained pooled estimate sizes of 0.51 for overall morbidity (95% CI, 0.11; 0.89/heterogeneity I 2 27.6%; Figure F) . Only one study, published by Elmoghazy et al had events regarding major complications (three events) or postoperative mortality (two events) among 11 cases reported, and thus, it was opted not to perform meta‐analysis.…”
Section: Resultsmentioning
confidence: 94%
“…For iCCA, four comparative studies (retrospective cohort studies) and nine noncomparative studies were included for analysis . For pCCA analysis, one comparative study (retrospective cohort) and nine noncomparative studies were included . Two records had data regarding both iCCA and pCCA …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, during this interval, no intrahepatic metastasis or peritoneal dissemination was revealed. LLR has been expanded to include minor resection, major resection, anatomical resection, donor hepatectomy (3), hepatectomy with thrombectomy (9), and radical resection for hilar cholangiocellular carcinoma (10). Moreover, recent studies have revealed the usability and safety of LLR in patients with liver cirrhosis (11) and those undergoing repeat hepatectomy (12).…”
Section: Discussionmentioning
confidence: 99%